Heligmosomoides bakeri: a model for exploring the biology and genetics of resistance to chronic gastrointestinal nematode infections - Behnke, Jerzy M.; Menge, David; Noyes, H.N. (Cambridge University Press, 2009)
The intestinal nematode Heligmosomoides bakeri has undergone 2 name changes during the last 4 decades. Originally, the name conferred on the organism in the early 20th century was Nematospiroides dubius, but this was dropped in favour of Heligmosomoides polygyrus, and then more recently H. bakeri, to distinguish it from a closely related parasite commonly found in wood mice in Europe. H. bakeri typically causes long-lasting infections in mice and in this respect it has been an invaluable laboratory model of chronic intestinal nematode infections. Resistance to H. bakeri is a dominant trait and is controlled by genes both within and outside the MHC. More recently, a significant QTL has been identified on chromosome 1, although the identity of the underlying genes is not yet known. Other QTL for resistance traits and for the accompanying immune responses were also defined, indicating that resistance to H. bakeri is a highly polygenic phenomenon. Hence marker-assisted breeding programmes aiming to improve resistance to GI nematodes in breeds of domestic livestock will need to be highly selective, focussing on genes that confer the greatest proportion of overall genetic resistance, whilst leaving livestock well-equipped genetically to cope with other types of pathogens and preserving important production traits.